Archaeology and Islam in Indonesia - Wood, Michael (Studia Islamika, 2008)
Some Indonesian archaeologists, however, have focused on the nation's Islamic past. Uka Tjandrasasmita is one of Indonesia's leading archaeologists and is largely behind the writing of Volume III of the Sejarah Nasional Indonesia, the national history that was the "standard text" for the teaching of history in Indonesian schools during the New Order; the volume he worked on dealt with Indonesia's Islamic history. For many years he held the position of the head of the Islamic Antiquities section of the Indonesian Archaeological Service (Bidang Arkeologi Islam, Pusat Penelitian Kepurbakalaan dan Peninggalan Nasional) and carried out survey and excavation work in West, Central and East java. He has published many reports on the Islamic archaeology of Indonesia.DOI: 10.15408/sdi.v15i2.530